Microbiological assessment of Nile tilapia Oreochromis niloticus collected from different super shops and local market in Dhaka, Bangladesh - Sarkar, Shilpi; Dey, Shuvra Kanty; Nipu, Md. Ashraful Islam; Brishti, Parsha Shanjana; Billah, Md. Baki (Journal of Fisheries, 2020)
The present study was conducted to detect the bacterial contamination of Nile tilapia Oreochromis niloticus collected from super shops and local market of Bangladesh. The sample specimens were collected from three super shops in Dhaka city viz. Agora, Shwapno and Prince Bazar and one local market (Savar Bazar). Samples were analysed to determine some pathogenic bacterial genera through the isolation and enumeration from different organs. The isolates were identified as Escherichia coli, Salmonella spp., Shigella spp. and Vibrio spp. by conventional culture method, biochemical tests and PCR assay. Total Viable Bacterial Counts (TVBC) were also determined. Fishes were found to be contaminated within a range between 6×104 to 1.6×106 cfu g–1. The load of E. coli and Shigella spp. were higher than that of Salmonella spp. and Vibrio spp. in all the studied samples. The study concludes that more precautions are required for personnel hygiene during fish processing and handling in order to prevent assemblage of pathogenic bacteria in super shops as well as local fish markets of Bangladesh.